Unmet Dental Care Need and Associated Barriers by Race/Ethnicity among US Adults. (April 2021) - Bhoopathi, V.; Luo, H.; Moss, M.; Bhagavatula, P.
Introduction: Ability to access needed dental care may vary among population subgroups. We assessed 1) the differences in the proportions of adults who reported unmet dental care needs in the past 12 months and the associated barriers (structural, financial, and cognitive) in 2015 to 2016 versus 2003 to 2004 by race/ethnicity and 2) the subgroups that are more likely to report unmet dental care needs. Methods: Data of 10, 029 respondents aged ≥19 y from the 2003–2004 and 2015–2016 National Health and Nutrition Examination Surveys were used. Chi-square tests assessed the differences in the proportions of adults who reported not getting the needed dental care between the periods. A multiple logistic regression model was run to identify characteristics that were significantly associated with unmet need after adjusting for other factors. Results: Overall, 19.4% of the adults reported an unmet dental care need in 2015 to 2016, as compared with 21% in 2003 to 2004. The overall unmet dental care need decreased only in the Hispanic groups (34% to 28%, P = 0.045) between 2003–2004 and 2015–2016. Between the periods, unmet need decreased among Hispanics aged 19 to 64 y (35% to 28%, P = 0.02), Hispanics with some college education or above (33.5% to 21.0%, P = 0.008), and nonpoor Hispanic adults (29.8% to 20.4%, P = 0.048). No significant differences were observed in the proportions of adults reporting structural ( P = 0.09), financial ( P = 0.86), or cognitive ( P = 0.07) barriers between the periods. When compared with their counterparts, nonelderly adults, women, Hispanics, adults with a high school education, those with less than a high school education, and poor adults were significantly more likely to report unmet dental care needs. Conclusions: Racial and ethnic disparities in accessing and receiving the needed dental care still exist. Financial barriers to dental care are the most commonly cited reasons for not getting the needed dental care. Knowledge Transfer Statement: The results of the study will inform policy makers, public health planners, and dental professionals about subgroups that still face difficulty in receiving the dental care they need. Policy makers should develop new policies to mitigate the financial barriers that are still prevalent. Dental professionals can mitigate the public's cognitive and financial barriers by educating the community through outreach programs and by providing services to low-income populations at reduced charges or through alternative payment plans.